2008
DOI: 10.1074/jbc.m801774200
|View full text |Cite
|
Sign up to set email alerts
|

BMP2 Regulates Osterix through Msx2 and Runx2 during Osteoblast Differentiation

Abstract: Osterix/Sp7, a member of the Sp1 transcription factor family, plays an essential role in bone formation and osteoblastogenesis. Although Osterix has been shown to be induced by BMP2 in a mesenchymal cell line, the molecular basis of the regulation, expression and function of Osterix during osteoblast differentiation, is not fully understood. Thus we examined the role of BMP2 signaling in the regulation of Osterix using the mesenchymal cell lines C3H10T1/2 and C2C12. Osterix overexpression induced alkaline phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
387
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 467 publications
(402 citation statements)
references
References 31 publications
13
387
1
1
Order By: Relevance
“…Interestingly, although expression of Osx in vivo requires Runx2, BMP-2 is still able to stimulate alkaline phosphatase activity and Osx expression in Runx2-deficient cells (18). Recent data indicate that BMP-2 activates expression of Osx through Runx2-dependent as well as -independent mechanisms involving Dlx5 and Msx2 (17,19). These studies also showed that BMP-2 induction of Osx required the transcriptional activation of Dlx5 by p38 MAPKmediated phosphorylation (17,20).…”
supporting
confidence: 48%
“…Interestingly, although expression of Osx in vivo requires Runx2, BMP-2 is still able to stimulate alkaline phosphatase activity and Osx expression in Runx2-deficient cells (18). Recent data indicate that BMP-2 activates expression of Osx through Runx2-dependent as well as -independent mechanisms involving Dlx5 and Msx2 (17,19). These studies also showed that BMP-2 induction of Osx required the transcriptional activation of Dlx5 by p38 MAPKmediated phosphorylation (17,20).…”
supporting
confidence: 48%
“…Secondly, RUNX2 directly regulates expression of osteocalcin (Matsubara et al , 2008). BMP2 is known to control the expression and functions of RUNX2 through Smad signaling, and a BMP2-Smad-RUNX2 axis in osteoblastogenesis has been established (Matsubara et al , 2008). However, our study showed that RUNX2 transcription levels in the B. mori dpp-expressing C3H10T1/2 target cells were not different from those in control cells and C3H10T1/2 cells transfected with the pCEP4 (Fig.…”
Section: Resultscontrasting
confidence: 49%
“…Osterix is thought to function downstream of RUNX2 during osteoblast differentiation (Choi et al , 2011;Matsubara et al , 2008). Recently, Matsubara et al (2008) obtained from the other 2 cell types. This result shows that the target cells expressed the B. mori dpp gene, and could be used to examine induction of osteogenic differentiation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations